The Effectiveness of Diaphragm Therapy on Physical and Psycho-Spiritual Comfort in COPD Patients in Cempaka Pavilion Room Jombang Hospital - AgustinaAgustina Maunaturrohmah; Endang Yuswatiningsih (STRADA : Jurnal Ilmiah Kesehatan, 2019)
Chronic Obstructive Pulmonary Disease (COPD) is a chronic infectious disease characterized by air flow resistance in the airways that is progressively non-reversible or partial reversible, this condition can cause patients to experience shortness of breath, giving rise to conditions of discomfort in body functions and patient limitations in carrying out activities daily. The aim of this study was to analyze the effectiveness of diaphragm therapy for the comfort of patients with chronic obstructive pulmonary disease (COPD). The design of this study was one group pre-post test. The population in this study were all patients in the Cempaka pavilion in Jombang General Hospital with an average of 26 patients per month. The sample in this study was 20 respondents using simple random sampling technique. Data collection using a questionnaire. Processing data using editing, coding, scoring, tabulating and analyzing data using statistical tests Paired Sample T Test with alpha 0.05.